Chocolate-on-White Ware: Typology, Chronology, and Provenance: The Evidence from Tell Abu al-Kharaz, Jordan Valley - Fischer, Peter M. (Bulletin of ASOR, 1999)
This study deals with the typology, chronology, and possible provenance of the Chocolate-on-White Wares from the settlement of Tell Abu al-Kharaz, Jordan Valley. Ten seasons of excavations produced 347 stratified vessels, which were included within the Chocolate-on-White Ware group as satisfying a number of listed criteria. Most of the bichrome-decorated and monochrome-decorated Chocolate-on-White Ware vessels were bowls, chalices, goblets, kraters, juglets and jugs, and jars. The wares were confirmed in Phases IV/1 and 2, V, and VI and include six subgroups: Proto-Chocolate-on-White Bichrome Ware; Chocolate-on-White Bichrome Ware; Eggshell Ware; and Chocolate-on-White I, II, and III. The chronological framework, which is supported by radiocarbon dates and cross-references with Cyprus, shows that the ware was produced from the late Middle Bronze Age IIB until the beginning of the Late Bronze Age IB. Absolute dates are offered. Trade and the possible provenance of the different wares are discussed. The petrographically analyzed samples point to two production areas: the Central Jordan Valley and southern Lebanon. Pottery synchronism and the terminology of burnished and unburnished bichrome-decorated pottery are considered.